Aplicação do Processo Analítico Hierarquico (AHP) Para Priorização de Obras de Intervenção em Áreas e Setores de Risco Geológico nos Municípios de Itapecerica da Serra e Suzano (SP) - de Paula, Beatriz Lima [UNESP]; Cerri, Leandro Eugenio da Silva [UNESP] (My University, 2012)
Municipal Plans of Risk Reducing (PMRR's) were produced in settlements in the municipalities of Itapecerica da Serra (SP) and Suzano (SP), covering areas at risk of landslides and washouts of banks of streams. The development of PMRR's provided the delimitation of areas of risk, the indication of intervention works in order to eliminate and / or reduce risks, and consequently an indication of the areas and priority sectors for implementation of intervention works. The prioritization of areas and sectors that should receive the works of reducing or eliminating risk was performed by an expert involved in risk mapping. Despite the specialist's judgment exercise caution, the decision regarding the priority sites for implementation of alternative interventions is subjective. Since there is no way to eliminate this subjectivity, the use of decision-making techniques is important to evaluate whether the expert's reasoning is consistent. One of the first techniques developed for multiple criteria is the AHP (Analytic Hierarchy Process). This paper describes the results of a research carried out in order to assess whether the use of Analytic Hierarchy Process contributes to the results of the indication of the areas and priority sectors for implementation of interventions can be considered more consistent than in situations where the priority occurs without the use of decision making techniques. Results were compared between the prioritization of interventions for implementation contained in PMRR's of Itapecerica da Serra and Suzano and those obtained from the use of Analytic Hierarchy Process (AHP). It was concluded that such techniques permits an evaluation of the expert's judgment is logically coherent, thus contributing to produce results more technically based.

Planos Municipais de Redução de Riscos (PMRR’s) foram elaborados em assentamentos precários dos municípios de Itapecerica da Serra (SP) e Suzano (SP), contemplando áreas de risco de escorregamentos e solapamentos de margens de córregos. A elaboração dos PMRR’s proporcionou a delimitação de setores de risco, a indicação de obras de intervenção para eliminar e/ou reduzir os riscos, bem como a indicação das áreas e setores prioritários para implantação das obras de intervenção. A priorização das áreas e setores que devem receber as obras de redução ou eliminação do risco foi realizada por especialista envolvido no mapeamento de risco. Apesar do julgamento deste especialista ser criterioso, a decisão quanto aos locais prioritários para implantação das alternativas de intervenção é subjetiva. Não há como eliminar essa subjetividade, mas o uso de técnicas de tomada de decisão possibilita avaliar se o raciocínio do especialista é coerente. Uma das primeiras técnicas desenvolvidas para múltiplos critérios é a AHP (Analytic Hierarchy Process), neste artigo denominado Processo Analítico Hierárquico. O presente artigo descreve os resultados de pesquisa realizada com o fim de verificar se a utilização do Processo Analítico Hierárquico contribui para que os resultados da indicação das áreas e setores prioritários para implantação de intervenções podem ser considerados mais coerentes do que nas situações em que a priorização se dá sem o emprego de técnicas de tomada de decisão. Foram comparados os resultados entre as priorizações para implantação de intervenções contidas nos PMRR’s dos municípios paulistas de Itapecerica da Serra e de Suzano e aqueles obtidos a partir da utilização do Processo Analítico Hierárquico (AHP). Concluiu-se que a utilização da técnica possibilita averiguar se o julgamento do especialista é logicamente coerente, contribuindo para a produção de resultados tecnicamente mais fundamentados.
Application of Analytic Hierarchy Process (AHP) in prioritization of works for intervention in Areas of Geological Risck in the cities of Itapecerica da Serra e Suzano (SP)
Keywords: Analytic Hierarchy Process (AHP); Decision making; Geological hazard; Slip; Washouts; analytical hierarchy process; decision making; hazard assessment; landslide; prioritization; washover; Brazil; Itapecerica da Serra; Sao Paulo [Brazil]